Plant trial production process and monitoring of crumb rubber concrete paver - Ling, Tung Chai; Md. Nor, Hasanan (2006)
In Malaysia, the amount of waste tyres is increasing due to increased number of vehicles. The waste tyres are produced every day, therefore the demand for more effective applications for recycling waste them is intense. This research studies the applicability of recycled waste tyres (crumb rubber) as a substitute for fine aggregate in concrete paver. Before the plant trial production, preliminary laboratory trials were conducted. The results in laboratory trials indicated that it is possible to cast paver containing crumb rubber up to 30 % of total sand volume. To promote a practical use and the acceptance of new material in concrete paver by potential end users, it is necessary to investigate manufacturing processes and feasibility of producing the crumb rubber concrete paver in a commercial plant setting. The produced pavers are assessed so that the performance of the pavers containing crumb rubber can be monitored and compared with those pavers made without crumb rubber.